Makeup and Costumes in the Welcome Dance of Sri Maharaja Ligor - Ayu Wanda Sari; Dwi Agrita Putri; Naufal Zhoriffalah Chaniago (Jurnal Pengetahuan dan Pendidikan, 2024)
This research examines the makeup and costumes in the dance "Sambut Sri Maharaja Ligor," a traditional dance originating from Indonesia. The aim of this study is to analyze the role of makeup and costumes in shaping the characteristics and meaning of the dance. The research method employed is qualitative research with data collection through direct observation and literature review. The findings reveal that makeup and costumes in the dance "Sambut Sri Maharaja Ligor" play a crucial role in creating the identity of the characters, conveying the story, and reinforcing the expression of movements. Makeup includes the use of facial makeup, masks, and other accessories that visually depict the characters' traits and social status within the narrative. Meanwhile, costumes encompass the choice of colors, designs, and materials that reflect the cultural aspects and aesthetic values of the dance's place of origin. This study provides a deeper understanding of the cultural and artistic values inherent in the makeup and costumes of "Sambut Sri Maharaja Ligor" dance, and offers insights for dancers, costume designers, and art researchers to comprehend and appreciate Indonesia's cultural richness.